Sustainable energy action plans at city level: A Portuguese experience and perception. (1st March 2018) - Coelho, Silvia; Russo, Michael; Oliveira, Ruben; Monteiro, Alexandra; Lopes, Myriam; Borrego, Carlos
Abstract: In order to achieve the targets underlined in the European Strategy for climate change and energy efficiency, the so called 20-20-20 package, the European Commission launched the Covenant of Mayors to endorse and support the efforts deployed by local authorities in the implementation of sustainable energy plans, and at the same time contribute to greenhouse gases emissions mitigation. This paper explores how the Covenant of Mayors (CoM) has been adopted in Portugal, and which type of measures are being defined and implemented by the municipalities. For that, all Sustainable Energy Action Plan (SEAP) submitted by Portuguese municipalities (124) have been examined, for which a detailed analysis was performed, including the Baseline Emission Inventory (70, i.e., around 50%). The municipalities that submitted SEAP cover 60% of the total population of the country because the main urban centres are a part of the 30% that have signed the CoM. Most common measures are related with changes on behaviour and infrastructure related to energy (such as renewable energies, energy efficiency in buildings, public lighting, etc.), waste and transport (for example optimization of: transport infrastructures, used vehicles and road operations). Public lighting is one of the energy measures present in all submitted SEAP, which plays a key role in energy consumption, reaching values of upwards of 12%, particularly in coastal areas due to higher population density and urban residential areas. Besides all efforts there is still a long way to go in terms of energy consumption reduction at local level.